Prevalence of fragrance contact allergy in the general population of five European countries: a cross‐sectional study. (1st December 2015) - Diepgen, T.L.; Ofenloch, R.; Bruze, M.; Cazzaniga, S.; Coenraads, P.J.; Elsner, P.; Goncalo, M.; Svensson, Å.; Naldi, L.
Summary: Background: Contact allergy to fragrances is assessed mostly in clinical populations of patients. Studies in the general population are scarce and vary in their methodology across countries. Objectives: To determine the prevalence of fragrance contact allergy in the European general population and to assess the clinical relevance of positive patch test reactions to different fragrances. Methods: In five European countries (Germany, Italy, the Netherlands, Portugal and Sweden) a random sample from the general population aged 18–74 years was drawn. In total, 12 377 subjects were interviewed in this cross‐sectional study and a random sample ( n = 3119) was patch tested using the TRUE Test and Finn Chamber techniques. Patch test procedures were harmonized by mandatory training before the study and monitoring during the study. Results: The highest prevalence for contact allergy of 2·6% [95% confidence interval (CI) 2·1–3·2] was found for fragrance mix (FM) I in petrolatum, with a high content of atranol and chloratranol, followed by 1·9% (95% CI 1·5–2·4) for FM II in petrolatum. The conservatively estimated prevalence of fragrance contact allergy was 1·9% (95% CI 1·5–2·5). This is defined as the existence of a positive patch test to FM I or FM II; any of their individual materials; Myroxylon pereirae ; sesquiterpene lactones or 3‐ and 4‐hydroxyisohexyl 3‐cyclohexene carboxaldehyde that show clinical relevance, defined conservatively as lifetime avoidance of scented products and an itchy skin rash lasting > 3 days in a lifetime. Using the reported lifetime prevalence of any contact dermatitis instead of the lifetime prevalence of any itchy skin rash, the prevalence is 0·8% (95% CI 0·5–1·2). The prevalence rates of contact allergy to fragrances in women are about twice those in men. Conclusions: This study helps to identify targets for prevention of fragrance allergy.